Street Posyandu: Early reproductive health promotion services and media for people in street situations - Erwin Rasyid; Subagio Subagio; Ahmad Syaifuddin; Firtya Maha Putri (Universitas Muhammadiyah Magelang, 2021)
The phenomenon of children on the streets is currently a severe problem in several cities in Indonesia. Women and children are the most vulnerable groups in the street community during the pandemic. Due to the complexity of people's health problems in street situations that are influenced by social and economic factors, this community service is expected to bridge the barriers to health access, especially reproductive health. This program aims to provide initial health services for people in street situations. Street Posyandu is expected to be a role model for the government and private sectors in dealing with people's health problems in street situations. The Street Posyandu program uses a persuasive approach. The technology used to support the Street Posyandu is the creation of a monitoring system and recording of maternal and child health conditions for street community. Posyandu Jalanan is realized by continuing to prioritize promotive and preventive services without neglecting curative (treatment) and rehabilitative (health restoration) aspects. The specific suggestion to be conveyed in this program is that the stakeholders need to redesign the form of health services aimed at communities in street situations.